Transcriptome analysis of the response of Hypomyces chrysospermus to cadmium stress - Wang, Yunan; Mao, Chunze; Shi, Yujia; Fan, Xuejing; Sun, Liping; Zhuang, Yongliang (Frontiers in Microbiology, 2022)
Hypomyces chrysospermus is a fungal parasite that grows on Boletus species. One isolated strain of H. chrysospermus from B. griseus was obtained and proved of strong ability to tolerate and absorb cadmium (Cd) by previous research. However, the molecular mechanisms of underlying the resistance of H. chrysospermus to Cd stress have not been investigated. This study aimed to assess the effect of Cd stress on the global transcriptional regulation of H. chrysospermus. A total of 1,839 differentially expressed genes (DEGs) were identified under 120 mg/l Cd stress. Gene ontology (GO) enrichment analysis revealed that large amounts of DEGs were associated with cell membrane components, oxidoreductase activity, and transport activity. KEGG enrichment analysis revealed that these DEGs were mainly involved in the translation, amino acid metabolism, transport and catabolism, carbohydrate metabolism, and folding/sorting and degradation pathways under Cd stress. Moreover, the expression of DEGs encoding transporter proteins, antioxidant enzymes, nonenzymatic antioxidant proteins, detoxification enzymes, and transcription factors was associated with the Cd stress response. These results provide insights into the molecular mechanisms underlying Cd tolerance in H. chrysospermus and serve as a valuable reference for further studies on the detoxification mechanisms of heavy metal-tolerant fungi. Our findings may also facilitate the development of new and improved fungal bioremediation strategies.